'Rule your condition, don't let it rule you': young adults' sense of mastery in their accounts of growing up with a chronic illness. Issue 1 (3rd July 2015) - Heaton, Janet; Räisänen, Ulla; Salinas, Maria
Abstract: Poor control of chronic illness is often attributed to patients' non‐adherence to medical advice and treatment. Policy and practice has traditionally focused on improving adherence, assuming that the more patients comply, the better their control and outcomes will be. Drawing on complexity theory, we question this logic in a secondary analysis of qualitative data from studies of young adults' experiences of growing up with a chronic illness. Examining their sense of mastery of their condition, we found they valued both being in medical control of their condition and having autonomy but had different ideas about how to achieve these goals. While some young adults mostly shared the traditional medical view that achieving good control was the key to retaining their autonomy, others saw control and autonomy as independent, non‐linear and potentially conflicting goals. The latter endeavoured to achieve both goals by striking a balance, variously adopting strategies of engagement with and resistance to their regime in the changing social contexts of their lives. We suggest that policy and practice needs to do more to promote autonomy and adaptive capacity, rather than simply maximising adherence and control, recognising the mundane complexity of living with and managing a chronic illness.